Processo de solidificação/estabilização de lodo têxtil em matriz de argila - influência do tipo de argila - Almeida, Paulo Henrique Souza (2009)
The clays are among the most important raw materials due to their numerous industrial functions. In the special case of the red ceramic industry, the clays have wide utility, the main product for the manufacture of ceramic tiles and blocks, which can be incorporated with industrial waste. Thus, the aim of this work was to study the influence of the different types of clays on the quality of ceramic blocks for sealing, with textile mud incorporated through the process of Solidification/Stabilization. It was evaluated the incorporation of textile mud in 5 types of clays which were collected in the North of the State of Paraná, and was done a qualitative analysis of ceramic blocks with 15% of textile mud in its composition in terms of its characteristics, set in the standards of Brazilian Association of Technical Standards. The mud used was colleted from 12 industrial laundries located in the region of Maringá - PR and characterized by Kaminata (2008) and Ramos (2009). The ceramic blocks were manufactured in small scale and tested for resistance to compression, leaching, solubilization and water absorption, according to their Brazilian standards. It was observed under the studied conditions that the blocks presented leaching and solubilization down the parameters. Therefore, the process of Solidification/Stabilization has been able to effectively immobilize the metals present in textile mud, showing itself as a promising process to minimize environmental impacts.